2014
DOI: 10.1007/978-3-642-53833-9_16
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm Strategies in the Food Industry

Abstract: Biofilms in food processing plants represent not only a problem to human health but also cause economic losses by technical failure in several systems. In fact, many foodborne outbreaks have been found to be associated with biofilms. Biofilms may be prevented by regular cleaning and disinfection, but this does not completely prevent biofilm formation. Besides, due to their diversity and to the development of specialized phenotypes, it is well known that biofilms are more resistant to cleaning and disinfection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 127 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…Therefore, novel and improved control approaches must be introduced to maintain the quality and safety of dairy products. A summary of a few emerging control strategies will be presented in this review and readers are directed to reviews dedicated to novel and emerging methods of biofilm control for a comprehensive insight into the subject ( Simões et al, 2010 ; Teixeira and Rodrigues, 2014 ).…”
Section: Biofilmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, novel and improved control approaches must be introduced to maintain the quality and safety of dairy products. A summary of a few emerging control strategies will be presented in this review and readers are directed to reviews dedicated to novel and emerging methods of biofilm control for a comprehensive insight into the subject ( Simões et al, 2010 ; Teixeira and Rodrigues, 2014 ).…”
Section: Biofilmsmentioning
confidence: 99%
“… Khadre et al (2001) have demonstrated that molecular ozone and its decomposition products, e.g., hydroxyl radicals, react with intracellular enzymes, nucleic materials and components of the cell envelope and spore coats to inactivate bacteria and, hence, disintegrate biofilms. However, despite having strong antimicrobial properties, ozone is unstable and quickly degenerates into its by-products, water and oxygen, before it can act on microorganisms ( Teixeira and Rodrigues, 2014 ).…”
Section: Biofilmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antimicrobial potential of coatings are relevant to their selfcleaning properties and can affect their use in surfaces used within food and medical environments [35,36]. Initial investigations were carried out on Ti-I coatings against E. coli (Fig.…”
Section: Resultsmentioning
confidence: 99%